Optimizing Teacher Working Groups in Improving the Competence of Islamic Religion Teachers in Rantau Selamat, East Aceh - Basri, Basri; Fitria, Fitria; Wahidah, Wahidah; Zainuddin, Zainuddin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2024)
Teachers as the main actors of educational success need to continuously improve their competence in order to innovate and be creative in teaching and learning to improve the quality of education in general. This study aims to find out the optimization strategy of the Teachers Working Group (KKG) of Rantau Selamat Sub-district and analyze how the success rate of KKG in improving the competence of PAI teachers in Rantau Selamat Sub-district? Through a qualitative approach, primary data were extracted from 8 informants. Data collection techniques were observation and structured interviews. The results showed that the optimization of the teachers' working group strategy in Rantau Selamat was carried out by strengthening the vision and mission of the organization, sharing knowledge and experience between senior and junior teachers, and training learning models such as calligraphy and music in PAI teaching. Optimizing KKG has had an impact on improving teachers' professionalism, pedagogical competence and skills. The teachers' working groups have been able to improve teachers' mastery of learning materials, syllabus preparation, learning methods, maximizing the use of facilities and infrastructure, and utilizing learning resources from Information Communication Technology (ICT). The implication of this research is that teachers' working groups need to be optimized to change the work culture and improve teachers' knowledge, competencies and performance so that the quality of education and learning processes in Aceh continues to improve.